Resource Center as Support System on Inclusive Education in Malang - Sinta Yuni Susilawati; Umi Safiul Ummah; Rizqi Fajar Pradipta; Dimas Arif Dewantara (Jurnal ORTOPEDAGOGIA, 2020)
National Special Supervisory School is a special school which is designed as a resource center by the government. Technically, Inclusive education needs supporting system that works as an institution that provides technical assistance to schools with special needs children. This study aims to discover, describe, in-depth analyze and also to find whether this study can be used as an input, consideration, direction and expansion of knowledge for related parties, especially with regard to (1) How is the resource center collaborative program with teachers on supporting inclusive education implementation in Malang. (2) What kind of assistances that resource center provided to teachers on supporting child-friendly inclusive education implementation in Malang (3) what kind of obstacles that the resource center had to face while supporting the inclusive education implementation in Malang. The result of this study shows resource center collaborative program in supporting Inclusive education implementation in Malang has been running and implemented well. Some assistances given by resource center in supporting inclusive education implementation in Malang include the main assistances in providing information/ guidance to schools with inclusive education, assessment assistances, educational guidance for special needs children, consulting assistances, training assistances for inclusive education teachers, providing ( producing) learning resources in the form learning books which later be printed out in Braille. On the human resource perspective, the supports from special teachers are still limited. Some obstacles that resource center had to face in order to support inclusive education implementation in Malang are limited in term of human resources and other limitations on media development assistances. This study concludes that the role of the Resource Center in supporting Inclusive Education implementation in Malang has been running and implemented well.